EVOLUTION OF TECHNOLOGY AND FRONTIERS IN SPANISH MILITARY GEOGRAPHY (1859-1936), GENERAL CONSIDERATIONS - REFOYO ACEDO, Enrique Javier (Journal of the Spanish Institute for Strategic Studies, 2023)
The industrial revolution not only took place in the factories of the growing European cities, but also occurred a military revolution which adapted for its purposes the inventions that were emerging. Likewise, industry and science also produced new weapons that opened other new possibilities of action to the military of all countries.Railroads were the ultimate key to the progress of the Great Powers in the economic, political and military modernity of the 19th and 20th centuries. The great motor-driven ships since the 19th century and the incredible aeronautical development since the 20th century were also part of these keys to economic, political and military power for the Great Powers.
Keywords: Technology; Evolution; Frontiers; Military Geography; States